INFLUENCE OF FIRE SAFETY SYSTEM, DESTINATION IMAGE, AND TOURIST SATISFACTION ON REVISIT INTENTION IN BADUNG REGENCY - I Nyoman , Indra Setiady; Nyoman, Diah Utari Dewi; Ida Ayu , Putu Sri Widnyani (KRISNA: Kumpulan Riset Akuntansi, 2025)
The objective of this study is to examine the impact of fire safety systems, destination image, and tourist satisfaction on revisit intention in Badung Regency. Badung Regency, a prominent tourist destination in Bali, confronts significant challenges in preserving the well-being, security, and reputation of the destination, thereby ensuring positive experiences for tourists and encouraging repeat visits. This study employs a quantitative approach using a survey method targeting 110 international and domestic tourists visiting Badung Regency. The collected data were then subjected to a rigorous analysis using multiple linear regression analysis. The findings suggest that the fire safety system exerts a positive and significant influence on revisit intention. Destination image exerts a substantial positive influence, while tourist satisfaction emerges as the predominant variable influencing revisit intention. These findings carry implications for destination managers and local governments, particularly in terms of enhancing fire safety systems, cultivating a positive image, and refining the quality of tourism services in Badung Regency. Keywords: fire safety system, destination image, tourist satisfaction, revisit intention